From morphological to ecological adaptation of the cornea in Oxudercinae fishes - Hu, Wenxian; Mu, Yuan; Wei, Chuanyu; Gai, Yulin; Zhang, Jie (Frontiers in Marine Science, 2022)
The outer cornea plays an important role in animal adaptation and survival in different environments. however, research on the morphological and ecological adaptation of corneal structure in amphibious fishes is limited. In this study, scanning electron microscopy (SEM) was used to evaluate the microstructure and adaptation of corneal epithelial cells in Oxudercinae. The results showed that the corneas of Oxudercinae species possess microridges, microvilli, and microplicae, as well as different numbers of epithelial cells. The morphological structure of corneal epithelial cells, observed by collecting samples and comparing the results with previous results, also showed different adaptive characteristics for moving between water and land. Further analyses revealed significant differences in epithelial cell density (F4, 22 = 5.436, P=0.003) and microridge width (F4, 22 = 8.392, P<0.001) among species with different levels of aquatic dependence. In addition, significant negative correlations of epithelial cell density with microridge width and separation width were confirmed (P<0.05). Interestingly, significant negative correlations of habitat type with cell density and microridges were uncovered, as well as a positive correlation between habitat type and separation width (P<0.05). The results indicated that the corneal structure of Oxudercinae species has characteristics of adaptation to an amphibious lifestyle.